Medical waste management in Turkey: A case study of Istanbul - Birpinar, Mehmet Ermin; Bilgili, Mehmet Sinan; Erdogan, Tugba (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The objective of this study was to analyze the present status of medical waste management in the light of the Medical Waste Control Regulation (MWCR) in Istanbul, the largest city in Turkey. About 17% of the hospitals, 20% of bed capacity, and 54% of private hospitals in Turkey are located in Istanbul. The first regulation about medical waste management in Turkey was published in 1993, and as a candidate state, it was changed in 2005 in accordance with EU Environmental Directives. In this work, a survey of 14 questions about the amount, collection, and temporary storage of medical wastes was applied to 192 hospitals in Istanbul through face-to-face interviews. It was found that the estimated quantity of medical waste from the hospitals is about 22 tons/day and the average generation rate is 0.63 kg/bed-day. Recyclable materials are collected separately at a rate of 83%. Separate collection of different types of wastes is consistently practiced, but 25% of the hospitals Still use inappropriate containers for medical waste collection. Almost 77% of the hospitals use appropriate equipment for the medical waste collection personnel. The percentage of the hospitals that have temporary storage depots is 63%. Medical waste management in Istanbul is carried out by applying the MWCR. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: JORDAN; Engineering; Environmental Sciences & Ecology